DAMPAK PENERAPAN ISO 15378 DALAM MEMPERTAHANKAN MANAJEMEN KUALITAS PRODUK TERHADAP FORECASTING TIME SERIES PENJUALAN OBAT DI CV. KIRANA CAHAYA SEJAHTERA KOTA GUNUNGSITOLI - Lase, Soterius; Zai, Kurniawan Sarototonafo; Kakisina, Sophia Molinda; Bate'e, Maria Magdalena (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2025)
This study aims to analyze the condition of quality management of medicinal products and evaluate the impact of the application of ISO 15378 in maintaining product quality management on forecasting time series drug sales in CV. Kirana Cahaya Sejahtera Gunungsitoli City. This type of research is to use quantitative research methods. Sampling techniques using probability sampling with a total of 75 people. From the results of the study, it was found that there was an impact or influence of the application of the impact of the application of ISO 15378 in maintaining product quality management on the Forecasting Time Series Drug Sales in CV. Kirana Cahaya Sejahtera Gunungsitoli City so that the hypothesis in this study was accepted. Based on the simple linear regression test, the results of F count of 17,468 were obtained with a significance/probability level of 0.000 <0.05. Therefore, it can be concluded that the regression model has an influence on the forecasting time series drug sales. Based on hypothesis testing it turns out that the application of ISO 15378 in maintaining product quality management has an impact on forecasting time series drug sales in CV. Kirana Cahaya Sejahtera Gunungsitoli City. Because based on the calculation of t-count> t-table, namely 2,326> 1,697.